Atomic-scale view of stability and degradation of single-crystal MAPbBr3 surfaces. Issue 36 (28th August 2019) - Choi, Joong Il Jake; Khan, Muhammad Ejaz; Hawash, Zafer; Kim, Ki Jeong; Lee, Hyunhwa; Ono, Luis K.; Qi, Yabing; Kim, Yong-Hoon; Park, Jeong Young
Abstract : MAPbBr3 (MA: CH3 NH3 + ) undergoes surface degradation under dark and vacuum conditions that leads to the formation of surface PbBr2 species. Abstract : While organic–inorganic hybrid perovskite solar cells are emerging as promising candidates for next-generation solar cells with fascinating power conversion efficiency, the instability of perovskites remains a significant bottleneck for their commercialization. An atomic scale understanding of the degradation of hybrid perovskites, however, is only in its beginning stages because of the difficulty in preparing well-defined surface conditions for characterization. Using atomic force microscopy at ultra-high vacuum and room temperature, we report the first direct observation of the degradation process of a cleaved methylammonium lead bromide, MAPbBr3 (MA: CH3 NH3 + ), single crystal. Upon in situ cleavage, atomic force microscopy images show large flat terraces with monolayer height steps, which correspond to the surface of cubic MAPbBr3 with methylammonium ligand termination. While this surface can be prepared via the cleavage process and is energetically stable, we observe that after several weeks under dark and vacuum conditions it degrades and produces clusters surrounded by pits. Guided by density functional theory calculations, we propose a degradation pathway that initiates even at low humidity levels and leads to the formation of surface PbBr2 species. We finally identify the electronic structure of the MA-bromine-terminated flat surface and find that it is correlated with a strong field-induced degradation of the MAPbBr3 only at positive sample bias voltages.